Writing African Christianity - Bongmba, Elias Kifon (Religion & theology, 2016)
In this overview of the historiography of Christianity in Africa a number of desiderata and considerations for future research are reviewed. The first issue considered relates to the practice of historiography. The second issue relates to African identity/-ies and its relationship to global cultural movements. The third desideratum is the pursuit of new disciplinary practices in the study of African Christianity, especially interdisciplinarity as scholarly ethos. Finally, a number of themes that should become foci in historiography of African Christianity are explored, among these are: concentration on local and regional narratives, the gendered character of Christianity in Africa, attention to the material conditions and needs of African religious communities and the various cultural innovations adopted to cope with these conditions, as well as the role of Christian communities in development in Africa and the wider encompassing question of ethics and morality.